Survey of Coronaviruses Infection among Patients with Flu-like Symptoms in the Golestan Province, Iran - Hossein Khani (Medical Laboratory Journal, 2018)
ABSTRACT Background and objectives: Coronaviruses are the main causes of respiratory tract infections in humans. They are also the second leading cause of common cold after rhinoviruses, and can lead to otitis media and asthma. The aim of this study was to investigate the molecular detection of coronaviruses in clinical samples of patients with flu-like symptoms. Methods: Specimens were taken from 297 patients with flu-like symptoms who were referred to the influenza laboratory of Golestan University of Medical Sciences during 2012-2014. RNA was extracted from the specimens using an RNA extraction kit. Accordingly, RNA was used for cDNA synthesis and GAPDH was used as the internal control. Synthesized cDNA was investigated for presence of human coronaviruses genome with real-time polymerase chain reaction using specific primers. Data were analyzed by SPSS 16.0 software. Results: The coronavirus genome was not detected in the specimens of patients with flu-like symptoms. Conclusion: Genome of human coronaviruses is absent in samples from patients with upper respiratory tract infections and influenza-like symptoms, which may indicate the low prevalence of the virus in the Golestan Province, Iran. KEYWORDS: Human coronaviruses, Upper respiratory tract infection, Golestan Province.